2020
DOI: 10.1177/2192568220903766
|View full text |Cite
|
Sign up to set email alerts
|

The Natural History of Ossification of Yellow Ligament of the Thoracic Spine on MRI: A Population-Based Cohort Study

Abstract: Purpose: To assess the natural history of ossification of yellow ligament (OYL) in the thoracic spine and determine risk factors for progression based on a longitudinal population-based cohort. Methods: A prospective, longitudinal cohort study was performed on a population-based cohort of Southern Chinese volunteers. T2-weighted magnetic resonance imaging (MRI) was used at baseline to identify any OYL and was verified with computed tomography. Follow-up MRI was performed 5 years later. Parameters under study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…Ossification of the posterior longitudinal ligament (OPLL) is also an important pathology. These ossification disorders are more common in Asians and may progress more aggressively [5]. These along with degenerative disc disease constitutes various non-traumatic and degenerative forms of cervical myelopathy and are commonly recognized under the umbrella term of degenerative cervical myelopathy (DCM) [6].…”
Section: Introductionmentioning
confidence: 99%
“…Ossification of the posterior longitudinal ligament (OPLL) is also an important pathology. These ossification disorders are more common in Asians and may progress more aggressively [5]. These along with degenerative disc disease constitutes various non-traumatic and degenerative forms of cervical myelopathy and are commonly recognized under the umbrella term of degenerative cervical myelopathy (DCM) [6].…”
Section: Introductionmentioning
confidence: 99%
“…As a multifactorial disease, obesity has been considered as an important risk factor associated with the pathogenesis of OLF ( 7 , 8 ). However, obesity-mediated genetic mechanism underlying OLF has not been fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…To date, genetic, mechanical stress, degeneration, inflammatory, and metabolic factors have been found to be involved in the occurrence and progression of OLF ( 2 6 ). Epidemiological studies indicated that a clinical subset of patients with obesity were more susceptible to early-onset or even diffuse OLF ( 7 ). Additionally, concrete evidence has identified obesity as an independent causal factor for the development of OLF in non-elderly adults ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…OSL typically occurs in Asians, especially the East Asian population, thereby indicating that genetic factors may play a vital role in its onset; however, many environmental factors, such as mechanical stress, metabolic disorders, gender, and age, may also contribute to the occurrence of OSL (5,6). A few researchers have recently begun to focus on the relationship of obesity or body mass index (BMI) with the onset or severity of OSL because the clinical practice has presented the susceptibility of OSL in the obese population, although the results of existing studies are contradictory (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Kobashi et al (6) showed that the BMI of the OPLL group is significantly higher than that of the non-OPLL group in both male (25.8 kg/m 2 vs. 23.3 kg/m 2 , P < 0.05) and female (25.9 kg/m 2 vs. 23.4 kg/m 2 , P < 0.05) individuals.…”
Section: Introductionmentioning
confidence: 99%